2015
DOI: 10.1517/17425247.2015.1046835
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced analgesic activity by cyclodextrins – a systematic review and meta-analysis

Abstract: The use of cyclodextrins can improve the efficacy of analgesic compounds, and they are an important tool in the search for greater analgesic effect. They may also be a way to reduce the therapeutic doses, and hence increasing the potential of the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 78 publications
0
21
0
Order By: Relevance
“…Clinical and preclinical evidence has shown that the pharmacological effects of analgesic and anti-inflammatory drugs are improved when complexed with CDs [76][77][78].…”
Section: Discussion Of Unusual Topics In Fibromyalgiamentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical and preclinical evidence has shown that the pharmacological effects of analgesic and anti-inflammatory drugs are improved when complexed with CDs [76][77][78].…”
Section: Discussion Of Unusual Topics In Fibromyalgiamentioning
confidence: 99%
“…Another study, also using the chronic noninflammatory widespread pain model in mice (an FM animal model), evaluated the effect of α-terpineol (Figure 4), both pure and complexed in β-CD, as CDs are useful tools in improving the pharmacological properties of terpenes [77,80].…”
Section: Discussion Of Unusual Topics In Fibromyalgiamentioning
confidence: 99%
“…Thus, the physicochemical properties of the drug (e.g., its solubility in water), the composition of the drug's formulation (e.g., aqueous or non-aqueous), and the physiological composition of the membrane barrier (e.g., the presence of an aqueous diffusion layer), will determine whether the CDs will enhance or will hamper the drug's delivery through a biological membrane (Loftsson, Masson & Brewster, 2004). This seems to be quite advantageous for natural non-polar compounds such as terpenes (Brito, Araujo, Quintans, Sluka & Quintans-Junior, 2015;Marques, 2010a;Pinho, Grootveld, Soares & Henriques, 2014a;Quintans et al, 2013b).…”
Section: Inclusion Methods and Complexation Efficiencymentioning
confidence: 99%
“…The formation of inclusion complexes increases the guest's in vivo stability against hydrolysis, oxidation, decomposition, and dehydration, as well as increasing their bioavailability (Brito, Araujo, Quintans, Sluka & Quintans-Junior, 2015;Oliveira, Guimaraes, Araujo, Quintans, Santos & Quintans-Junior, 2015;Loftsson & Duchene, 2007).…”
Section: Cyclodextrins (Cds)mentioning
confidence: 99%
“…These preclinical studies also showed greater bioavailability of the drug with reduced side effects. [15] Since ancient times, honey was valued as a flavorful sweetener. It also has an extensive history of traditional medicinal use.…”
Section: Original Articlementioning
confidence: 99%